Duration as a strategic interest rate risk management tool in financial institutions - Van Vuuren, Gary Wayne (North-West University, 2005)
Banks and financial institutions record core banking activities (taking deposits and making loans) on the balance sheet of the banking book, but trading book (trading and investment) pursuits are recorded off-balance-sheet. Both books are subject to considerable risk from numerous sources, but regulatory capital reserves - to shield from unexpected market moves - are not required for the banking book as they are for the trading book. Both of these substantial shortcomings will be addressed in the near future. The 2005 initiation of new global accounting standards will ensure that trading book derivative fair values are recorded and reported on the balance sheet while the new Basel accord, due for full implementation in 2007, will regulate the calculation and reservation of capital required for the banking book. These changes are expected to better regulate and manage the transparency of financial institutions' activities and so prevent large scale economic disasters or deliberate corporate fraud. Institutions not compliant with the new rules will face severe financial losses, regulatory fines and possible debilitating legal action. One of the most commonly-used tools for measuring and managing interest rate risk, the Macaulay duration, has enjoyed almost unchallenged success, but it employs severely restrictive and unrealistic assumptions which constrain its usefulness and reliability in the rapidly-changing world of defaultable securities, those with embedded derivatives and instruments with perpetual maturities. Robust measures which more accurately approximate interest rate risk by relaxing unrealistic assumptions are required. Applications which significantly improve the accuracy of the Macaulay duration are considered as well as a new look at the duration problem in general. The influence of a more accurate duration measure on duration gap provides a significantly improved economic Market Value of Equity. The role of this enhanced measure is crucial for risk management as well as regulatory and accounting compliance.
Thesis (Ph.D. (Risk Management))--North-West University, Potchefstroom Campus, 2005.